Juridical Analysis of Prohibition of Monopoly and Unfair Business Competition in Wholesaler Procedures for Sales of Umrah Tickets by PT. Garuda Indonesia (Persero) Tbk - Redati Tsaniya Sekarsari; Siti Malikhatun Badriyah (Melayunesia Law, 2023)
The Business Competition Supervisory Commission (KPPU) decided that PT. Garuda Indonesia (Persero) Tbk. committing violations related to discrimination and making efforts to close access to distribution channels for direct sales of Umrah tickets to and from Jeddah and Medina through the Wholesaler Program. Where is PT. Garuda issued a policy regarding Middle East Asia (MEA) ticket sales that required Umrah Pilgrimage Organizers (PPIU) to purchase through the six designated wholesalers. The purpose of this research is to find out the legal consequences of the practice of prohibiting monopoly in the wholesaler procedure for selling Umrah tickets by PT. Garuda Indonesia (Persero) Tbk. This study uses a normative juridical research method using a statutory approach (Statutes Approach), namely Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition and a case approach (Case Approach), namely Decision Number 06/KPPU-L/ 2020 regarding Alleged Discriminatory Practices of PT Garuda Indonesia (Persero).